Efeito do metilfenidato em ratos jovens submetidos ao modelo de epilepsia com pilocarpina - Linhares, Maria Isabel (2017)
Methylphenidate (MFD) is the drug used for Attention Deficit/Hiperactivity Disorder (ADHD). In the clinic, there is a prevalence of ADHD in patients with epilepsy, being identified as a common comorbidity. The FDA warns against the use of MFD in patients with epilepsy. In this way, it is resolved to investigate in more depth the possible activity of MFD in patients with epilepsy. The objective is to evaluated the effect of MFD on young rats submitted to the pilocarpine epilepsy model. Pilocarpine (PILO) was administered in young animals, at 21 days of age, at a dose of 320 mg/Kg (P320), intraperitoneal (i.p.) for induction of the epilepsy model. Behavioral crises were classified according to the Racine scale and the duration of SE (status epilepticus) was controlled with diazepam (DZ, 4mg / Kg, i.p., 60 minutes post induction). During 21 days, the animals received the MFD at doses of 2,5; 5 and 10mg/Kg and saline (SAL), 10 mL/Kg. Behavioral tests, oxidative stress assessment, TNF-α dosing, and expression analysis of COX-2 and iNOS were performed. In the open field test, an increase in locomotor activity was observed in all analyzed doses of epileptic animals. Did not change the number of rearing. The results analyzed in the high cross maze test showed that MFD increased the parameters, NEOA, at doses of 2,5; 5 and 10 mg/Kg and PEOA and PTOA at doses of 5 and 10 mg/Kg in epileptic animals. In the forced swim test, MFD decreased immobility time at all doses analyzed in epileptic and non epileptic animals. In the Y-maze test (short-term memory) there was a decrease in spontaneous alternations at doses of 2,5; 5 and 10 mg/Kg epileptic animals. In the Object Recognition test (long-term memory) there was no change in any dose of MFD. The evaluation of the oxidant actvity showed that MFD increased levels of lipid peroxidation and nitrite / nitrate, and decreased the activity of GSH and catalase. There was a decrease in AChE activity in the hippocampus and prefrontal cortex. There was an increase in myeloperoxidase activity (a biomarker of inflammation) in MFD treatment. MFD increased the levels of TNF-α induced by P320 in the hippocampus, striatum and prefrontal cortex, reinforced by the effects observed through the activity of COX-2 and iNOS, which showed increased labeling for these enzymes in the striatum. Determination of monoamine levels showed that MFD increased dopamine (DA) levels and decreased DOPAC levels in epileptic animals. In vitro experiments showed that MFD caused increased cell viability in the MTT test. The MFD presented possible pro-oxidant and pro-inflammatory actions, as well as a neuroinflammation. The MFD demonstrated a potential for anxiolytic and antidepressant activity and presented a pro-oxidant and pro-inflammatory action seen through the model of epilepsy induced by pilocarpine in young rats.